The management of fevers in Kenyan children and adults in an area of seasonal malaria transmission. - Guyatt, H; Snow, R (2004)
This study investigates the source, timing and types of treatment for fevers across all ages in a low malaria-transmission area of Kenya. The period prevalence for fever, and subsequent treatment seeking behaviour, was similar across all ages. The use of the informal retail sector was common (47% of first actions), though most visits to shops and chemists (77%) resulted in treatment with an antipyretic not an antimalarial. The major source of the first line recommended drug, sulfadoxine-pyrimethamine (SP), was at the formal health sector, and 32% of fevers made at least one visit to a health care facility. Although only 7% of fevers received SP within 24 hours of fever onset, 27% ultimately received treatment with this antimalaria. It is estimated that of the total amount of SP consumed in this population, only 20% is administered to children less than 5 years old. In this area of Kenya disease risks decline with increasing age, however, adult populations consume over 40% of prescribed or purchased anti-malarial drugs. In light of the proposed new, more costly anti-malarial drug combinations these findings have major implications for the effective allocation of limited financial resources at household and government levels.